PENERAPAN METODE FMEA (FAILURE MODE AND EFFECT ANALYSIS) UNTUK KUANTIFIKASI DAN PENCEGAHAN RESIKO AKIBAT TERJADINYA LEAN WASTE - Surya Andiyanto; Agung Sutrisno; Charles C Punuhsingon (JURNAL POROS TEKNIK MESIN UNSRAT, 2017)
ABSTRACK Waste is an activity that absorbs or wasting of resources such as time or added expenses but do not add any value in activities. Each production process generally have opportunities for waste generation, especially on fast-food restaurants. To avoid or minimize the occurrence of such waste, waste analysis is needed. Waste analysis performed in this study using the application of FMEA method to determine waste criticality. From the result of the study, waste related to delivery process is becoming the most criticality waste with WPN at 99.16. Keywords: Waste, FMEA, WPN (Waste Priority Number), Fast Food Industry.